Strengthening biosafety and biotechnology application in Eastern and Southern Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Following a regional biosafety meeting held in Harare in October 1993 with the support of DGIS, the Netherlands, 14 Eastern and Southern African countries have established a Regional Biosafety Focal Point (RBFP). The goal of RBFP is to promote...